Production process of motor package for passenger car

CN122896336APending Publication Date: 2026-10-13HUBEI GISSING AUTO PARTS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611222918.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-12
Publication Date
2026-10-13

AI Technical Summary

Technical Problem

[0005]本发明的目的在于提供一种乘用车电机包裹件的生产工艺,解决了现有技术中因化学发泡泡孔粗大且分布不均导致中高频吸声系数偏低的问题

Benefits of technology

[0034]本发明的一种乘用车电机包裹件的生产工艺,采用超临界CO2物理发泡替代传统PU化学发泡,通过均相成核与快速降压发泡机制实现泡孔结构的精细化调控,泡孔平均直径由传统PU发泡的50~150μm细化至3~15μm且孔径分布均匀,克服了化学发泡泡孔粗大且分布不均的固有缺陷;同时,本发明制备的TPU微孔隔音垫闭孔率≥95%,细密且高度闭孔的泡孔结构大幅增加了声波在材料内部传播时的反射界面和迂曲路径,声波在孔壁间反复反射耗散,显著提升了材料在中高频段的粘性耗散和热传导效率,成品在800~4000Hz频段内的平均垂直入射吸声系数≥0.6,相较于传统PU发泡材料提升显著,有效解决了现有包裹件中高频吸声性能不足的技术难题;此外,本发明采用“预制发泡板材+热压成型”的两段式工艺路线,将耗时较长的超临界浸渍发泡工序与快速热压成型工序解耦,单件成型周期大幅缩短,适合乘用车电机包裹件的大批量工业化生产,且超临界CO2发泡过程无有机溶剂和化学发泡剂残留,工艺清洁环保。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122896336A_ABST
    Figure CN122896336A_ABST
Patent Text Reader

Abstract

This invention relates to the field of motor wrapping component manufacturing technology, and discloses a manufacturing process for passenger vehicle motor wrapping components, comprising: drying TPU granules at 80-95℃ to a moisture content ≤0.05wt%; melting and extruding the dried TPU granules into TPU sheets with a thickness of 3-5mm; placing the TPU sheets in a high-pressure reactor, introducing CO2 and adjusting to a supercritical state, and performing saturated impregnation treatment at 32-45℃ and 10-18MPa for 12-36 hours; reducing the pressure inside the reactor to atmospheric pressure at a depressurization rate of 2-15MPa / s to trigger foaming and obtain a foamed preform; hot-pressing the foamed preform at 80-120℃ to form a motor wrapping component blank; and cooling and shaping to obtain the finished product. This invention uses supercritical CO2 foaming technology to replace traditional PU chemical foaming, and the resulting wrapping component has a density of 25-35kg / m³. 3 The average cell diameter is 3~15μm, the closed-cell rate is ≥95%, and the sound absorption coefficient in the mid-to-high frequency band of 800~4000Hz is ≥0.6, which effectively solves the problems of large and uneven cell size and poor mid-to-high frequency sound absorption performance of existing PU foam wrapping parts.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of motor enclosure manufacturing technology, and in particular to a manufacturing process for a passenger vehicle motor enclosure. Background Technology

[0002] The NVH performance of passenger vehicle electric drive systems directly affects overall vehicle comfort. As a key acoustic enclosure component, the quality of the motor enclosure's sound absorption and insulation performance determines the level of noise transmitted from the powertrain to the passenger compartment. With the continuous increase in the speed of electric motors in new energy vehicles (generally reaching 12,000~20,000 rpm), the energy of electromagnetic and mechanical noise from the motor is concentrated in the mid-to-high frequency range (800~4000Hz), placing higher demands on the sound absorption performance of the enclosure in this frequency band. Currently, passenger vehicle motor enclosures are mainly prepared using polyurethane (PU) foam material through in-mold chemical foaming molding. This type of material has advantages such as light weight and the ability to be molded into complex shapes, and it already has a relatively wide application base in the field of automotive sound insulation.

[0003] Current manufacturing processes for PU foamed components typically employ chemical foaming. However, this process has inherent drawbacks: the decomposition rate of the chemical foaming agent is significantly affected by temperature and time; bubble nucleation and growth during foaming are difficult to control precisely; and the resulting foam structure exhibits a wide pore size distribution (typically 50-150 μm), uneven pore size, and inconsistent pore wall thickness. Acoustically, this coarse and uneven pore structure means that when sound waves are incident, the large pores provide limited viscous dissipation and heat conduction paths. Sound waves penetrate directly between the thicker pore walls rather than undergoing repeated reflections and attenuation within the material, resulting in a generally low sound absorption coefficient (typically ≤0.5) in the mid-to-high frequency range.

[0004] In addition, the chemical foaming reaction of PU is accompanied by the formation of cross-linked structures such as urea bonds and biuret. The reaction is highly exothermic, and the uneven temperature distribution inside thick-walled products further aggravates the non-uniformity of the cell structure. At the same time, the decomposition residues of chemical foaming agents also have an adverse effect on the long-term acoustic stability and environmental protection of the material. Summary of the Invention

[0005] The purpose of this invention is to provide a manufacturing process for motor enclosures in passenger vehicles, which solves the problem of low mid-to-high frequency sound absorption coefficient caused by large and unevenly distributed pores in chemical foaming in the prior art.

[0006] To achieve the above objectives, the present invention provides a manufacturing process for a passenger vehicle motor enclosure, comprising the following steps:

[0007] The TPU granules were dried at 80~95℃, and the moisture content of the dried granules was controlled to be ≤0.05wt%.

[0008] The dried TPU granules are melt-extruded and molded into TPU sheets with a thickness of 3-5mm;

[0009] The TPU sheet was placed in a high-pressure reactor, CO2 was introduced and adjusted to a supercritical state, and saturated impregnation was performed at 32~45℃ and 10~18MPa for 12~36h.

[0010] After saturated impregnation, the pressure inside the reactor is reduced to atmospheric pressure at a depressurization rate of 2~15MPa / s to trigger the foaming of the TPU sheet and obtain the foamed preform.

[0011] The foamed blank is placed in a molding mold and heated and pressurized at 80~120℃ to form a motor wrapping blank;

[0012] The hot-pressed motor wrapping blank is cooled to room temperature to obtain the finished motor wrapping for passenger vehicles.

[0013] The specific steps for drying the TPU granules at 80~95℃ include:

[0014] The TPU granules are fed into a hot air circulating drying equipment and heated to 80-95℃ at a rate of 5-10℃ / min.

[0015] Dry at a constant temperature of 80~95℃ for 6~12 hours. During the drying process, dry air is introduced to remove the moisture volatilized from the surface and inside of the granules.

[0016] After drying is complete, stop heating and cool the TPU granules to 40~60℃ in a dry air atmosphere before discharging. Seal and store the material and put it into the extrusion process within 4 hours.

[0017] The step of melting and extruding the dried TPU granules specifically includes:

[0018] The dried TPU granules are added to a single-screw extruder and melted and plasticized by multi-stage heating: feeding section 170~180℃, melting section 185~195℃, and homogenization section 180~190℃.

[0019] After molten TPU is extruded through a flat die, it is rolled and shaped by a three-roll calender, and the thickness deviation of the sheet is controlled to be ≤±0.1mm to obtain a continuous TPU sheet.

[0020] Cut the continuous TPU sheet into rectangular sheets that match the inner cavity of the high-pressure reactor, let it stand to room temperature, and then clean off any surface dust.

[0021] The method specifically includes the following steps: placing the TPU sheet in a high-pressure reactor, introducing CO2 and adjusting it to a supercritical state, and performing saturated impregnation treatment at 32-45°C and 10-18 MPa.

[0022] The cut TPU sheets are laid flat in layers on the material rack of the high-pressure reactor, with a gap of 2-5mm between the layers. The reactor body is sealed and the airtightness test is completed to confirm that the leakage rate is ≤0.01MPa / h.

[0023] Liquid CO2 is introduced into the reactor, and the pressure is gradually increased to 10-18 MPa at a rate of 0.5-1 MPa / min, while the temperature is increased to 32-45℃ at a rate of 1-2℃ / min, so that the CO2 in the reactor reaches a supercritical state.

[0024] Maintain constant temperature and pressure, and hold the pressure for 12~36 hours to allow supercritical CO2 to fully diffuse and uniformly dissolve inside the TPU matrix, forming a polymer-gas homogeneous system.

[0025] The step of reducing the pressure inside the vessel to atmospheric pressure at a rate of 2-15 MPa / s after saturated impregnation specifically involves:

[0026] After saturated impregnation is completed, the pressure relief valve of the vessel is opened, and the pressure relief process is controlled by the flow regulating valve to reduce the pressure inside the vessel to atmospheric pressure at a constant pressure reduction rate of 2~15MPa / s.

[0027] CO2 dissolved in the TPU matrix is ​​released instantly due to a sudden drop in solubility, forming a large number of uniform bubble nuclei and growing to obtain a microporous foamed preform.

[0028] The step of placing the foamed preform into a molding die and heating and pressing it specifically includes:

[0029] Place the foamed preform flat into the mold cavity preheated to 80~120℃, and keep it at the preheated temperature for 10~30s after closing the mold.

[0030] Hold the molded material at a molding pressure of 0.3~1.0MPa for 30~120s to make the foamed preform conform to the surface of the mold cavity and form a wrapping shape that matches the motor contour.

[0031] After the pressure holding is completed, the pressure is released at a rate of 0.1~0.2MPa / s. After the pressure returns to zero, the mold is opened and the motor wrapping blank is taken out.

[0032] In the step of cooling the hot-pressed motor wrapping blank to room temperature, air cooling is used for cooling and shaping. The cooling wind speed is controlled at 2~5m / s, so that the motor wrapping blank is cooled to 20~25℃ within 10~15min. During the cooling process, the blank is fixed with shaping fixtures to prevent cooling deformation.

[0033] The density of the finished passenger vehicle motor enclosure is 25~35 kg / m³. 3 The average pore diameter is 3~15μm, and the closed-cell rate is ≥95%.

[0034] This invention discloses a manufacturing process for a passenger vehicle motor enclosure, employing supercritical CO2 physical foaming instead of traditional PU chemical foaming. Through homogeneous nucleation and rapid pressure reduction foaming mechanisms, the process achieves refined control of the cell structure, reducing the average cell diameter from 50-150 μm in traditional PU foaming to 3-15 μm with uniform pore size distribution. This overcomes the inherent defects of large and unevenly distributed pores in chemical foaming. Simultaneously, the TPU microporous sound insulation pad prepared by this invention exhibits a closed-cell rate ≥95%. The dense and highly closed-cell structure significantly increases the reflection interface and tortuous path of sound waves propagating within the material. Repeated reflection and dissipation of sound waves between the pore walls significantly improves sound insulation. The material exhibits improved viscous dissipation and thermal conductivity efficiency in the mid-to-high frequency range. The average vertical incident sound absorption coefficient of the finished product in the 800~4000Hz frequency range is ≥0.6, which is significantly improved compared with traditional PU foam materials, effectively solving the technical problem of insufficient high-frequency sound absorption performance in existing packaging components. In addition, the invention adopts a two-stage process route of "pre-made foamed board + hot pressing molding", decoupling the time-consuming supercritical impregnation foaming process from the rapid hot pressing molding process, greatly shortening the single-piece molding cycle. It is suitable for the mass industrial production of passenger car motor packaging components, and the supercritical CO2 foaming process leaves no organic solvents or chemical foaming agents residues, making the process clean and environmentally friendly. Attached Figure Description

[0035] To more clearly illustrate the technical solutions in the embodiments of this application or the prior art, the accompanying drawings used in the description of the embodiments or the prior art will be briefly introduced below.

[0036] Figure 1 This is a flowchart of the manufacturing process of the passenger vehicle motor enclosure component of the present invention. Detailed Implementation

[0037] The embodiments of the present invention are described in detail below. Examples of the embodiments are shown in the accompanying drawings. The embodiments described below with reference to the accompanying drawings are exemplary and intended to explain the present invention, but should not be construed as limiting the present invention.

[0038] Please refer to Figure 1 , Figure 1 This is a flowchart of the manufacturing process for the passenger vehicle motor enclosure of the present invention. The present invention provides a manufacturing process for a passenger vehicle motor enclosure, including the following steps:

[0039] S1: Dry the TPU granules at 80~95℃, and control the moisture content of the dried granules to ≤0.05wt%.

[0040] Specifically, S11: The TPU granules are fed into a hot air circulating drying equipment and heated to 80-95℃ at a rate of 5-10℃ / min. S12: Dry at a constant temperature of 80~95℃ for 6~12 hours. During the drying process, dry air is introduced to remove the moisture volatilized from the surface and inside of the granules. S13: After drying is complete, stop heating, cool the TPU granules to 40~60℃ in a dry air atmosphere, discharge them, seal and store them, and put them into the extrusion process within 4 hours.

[0041] In this embodiment, controlling the moisture content is a crucial prerequisite for ensuring the quality of subsequent supercritical CO2 foaming. TPU, as a highly polar polymer, has ester or ether groups in its molecular chain that have a high affinity for moisture, easily adsorbing it from the environment. When the moisture content of TPU granules exceeds 0.05 wt%, the residual moisture will occupy the free volume of the polymer matrix in the high-temperature (32~45℃) and high-pressure (10~18MPa) supercritical CO2 environment, reducing the equilibrium solubility and diffusion coefficient of CO2 in TPU, leading to a decrease in saturated impregnation efficiency. Simultaneously, moisture will act as a heterogeneous nucleating agent in the subsequent rapid depressurization foaming stage, inducing heterogeneous bubble nucleation. Furthermore, the vapor pressure generated by moisture vaporization will interfere with the homogeneous nucleation mechanism of CO2 precipitation, causing abnormally large pores and a bimodal pore size distribution in the cell structure. Therefore, reducing the moisture content to below 0.05 wt% through high-temperature hot air circulation drying at 80~95℃ for 6~12 hours can minimize the negative impact of moisture on cell uniformity.

[0042] S2: The dried TPU granules are melted and extruded to form TPU sheets with a thickness of 3~5mm.

[0043] Specifically, S21: The dried TPU granules are added to a single-screw extruder and melted and plasticized through multi-stage heating at 170~180℃ in the feeding section, 185~195℃ in the melting section, and 180~190℃ in the homogenization section.

[0044] S22: After molten TPU is extruded through a flat die, it is rolled and shaped by a three-roll calender and the thickness deviation of the sheet is controlled to be ≤±0.1mm to obtain a continuous TPU sheet;

[0045] S23: Cut the continuous TPU sheet into rectangular sheets that match the inner cavity of the high-pressure reactor, let it stand to room temperature, and then clean off any surface dust.

[0046] In this embodiment, a single-screw extruder is used to prepare TPU sheets, with the extrusion temperature controlled in three gradient stages. The feeding stage (170-180℃) ensures that the granules soften but do not melt and stick together, which is beneficial for stable material transport. The melting stage (185-195℃) is the highest temperature range, allowing the TPU to completely melt and have good fluidity, facilitating homogenization and mixing. The homogenization stage (180-190℃) is slightly lower than the melting stage temperature, which helps reduce melt pressure fluctuations, stabilize the extrusion flow rate, and avoid the TPU from staying in the high-temperature zone for too long, leading to thermal degradation. The sheet thickness is controlled at 3-5mm with a thickness deviation of ≤±0.1mm to ensure that the diffusion distance of CO2 in the thickness direction of the sheet is relatively consistent during the subsequent supercritical impregnation process. If the thickness deviation is too large, the CO2 saturation level will differ between different sheets processed in the same batch, directly affecting the consistency of the cell structure after foaming. The sheet is cut into rectangular sheets that match the inner cavity of the high-pressure reactor. This is to maximize the utilization of the reactor's internal volume and to prevent the sheets from being freely placed inside the reactor, which would obstruct the CO2 gas flow channel and affect the impregnation uniformity.

[0047] S3: Place the TPU sheet in a high-pressure reactor, introduce CO2 and adjust it to a supercritical state, and perform saturated impregnation treatment at 32~45℃ and 10~18MPa for 12~36h.

[0048] Specifically, S31: The cut TPU sheets are laid flat in layers on the material rack of the high-pressure reactor, with a gap of 2~5mm between the layers. The reactor body is sealed and the airtightness test is completed to confirm that the leakage rate is ≤0.01MPa / h.

[0049] S32: Liquid CO2 is introduced into the reactor and the pressure is gradually increased to 10-18 MPa at a rate of 0.5-1 MPa / min, while the temperature is increased to 32-45℃ at a rate of 1-2℃ / min, so that the CO2 in the reactor reaches a supercritical state.

[0050] S33: Maintain constant temperature and pressure, hold pressure for 12~36h to allow supercritical CO2 to fully diffuse and uniformly dissolve inside the TPU matrix, forming a polymer-gas homogeneous system.

[0051] In this embodiment, the TPU sheets are laid out in layers with a 2-5mm gap between each layer. This allows supercritical CO2 to diffuse simultaneously from the top and bottom surfaces of the sheets into the interior, shortening the saturation time and preventing adjacent sheets from sticking together due to surface softening under high pressure. A leakage rate of ≤0.01MPa / h is ensured to maintain pressure stability in the reactor during the 12-36h pressure holding process. Excessive leakage would require continuous pressurization, increasing energy consumption, and pressure fluctuations would interfere with the CO2 dissolution equilibrium in the TPU, affecting the consistency of the saturation state. A pressurization rate of 0.5-1MPa / min and a heating rate of 1-2℃ / min are used because the TPU sheets have not yet reached saturation in the initial stages of pressurization and heating. At this time, CO2 has not fully penetrated and plasticized the TPU molecular chains, and the TPU is still in a glassy state or a low-elasticity state in the early stages of softening, making it less resistant to deformation. If the pressurization rate is too fast (e.g., >2MPa / min), the sheet surface will be subjected to high-pressure fluid impact in a very short time, potentially causing non-uniform compression deformation. Meanwhile, the heat of compression of supercritical CO2 can cause the temperature inside the reactor to exceed the set value instantly, further aggravating the thermo-mechanical coupling deformation of the TPU matrix. Therefore, a slower rate of pressurization and heating allows CO2 to permeate and pressurize simultaneously, and the TPU is gradually plasticized and softened by CO2. The matrix can respond to changes in external pressure with uniform volume compression, avoiding warping or collapse caused by local stress concentration.

[0052] S4: After saturated impregnation, the pressure inside the reactor is reduced to atmospheric pressure at a rate of 2~15MPa / s to trigger the foaming of the TPU sheet and obtain the foamed blank.

[0053] Specifically, S41: After saturated impregnation is completed, open the pressure relief valve of the vessel body, and control the pressure relief process through the flow regulating valve to reduce the pressure inside the vessel to atmospheric pressure at a constant pressure reduction rate of 2~15MPa / s;

[0054] S42: CO2 dissolved in the TPU matrix is ​​released instantly due to a sudden drop in solubility, forming a large number of uniform bubble nuclei and growing to obtain a microporous foamed preform.

[0055] In this embodiment, the sudden pressure drop inside the autoclave causes a sharp increase in the chemical potential of CO2 in TPU, resulting in a rapid increase in thermodynamic supersaturation and the system entering a highly unstable supersaturated state. This process controls the depressurization rate within the range of 2–15 MPa / s, ensuring a high nucleation density (pore size 3–15 μm) while avoiding the following problems that may occur with excessively rapid depressurization (>15 MPa / s): First, the rapid expansion and exothermic reaction of the gas inside the autoclave may cause a sudden drop in the local temperature of the TPU matrix, potentially leading to a glassy state and limiting cell growth; second, the high-speed gas flow may entrain turbulence marks on the molten TPU surface, affecting surface quality; and third, the pressure relief valve and pipelines may be subjected to excessive impact loads, reducing equipment lifespan. The depressurization rate can be flexibly adjusted within the 2–15 MPa / s range according to the target density and pore size requirements—lower rates (2–5 MPa / s) are suitable for preparing lower densities (close to 25 kg / m³). 3 For products with larger pore sizes (close to 15 μm), higher processing speeds (10~15 MPa / s) are suitable for preparing products with higher densities (close to 35 kg / m³). 3 Products with smaller pore sizes (close to 3μm) provide room for parameter adjustment in actual production.

[0056] S5: Place the foamed blank into a molding mold and heat and press it at 80~120℃ to form a motor wrapping blank.

[0057] Specifically, S51: Place the foamed preform flat into the mold cavity preheated to 80~120℃, and keep it at the preheated temperature for 10~30s after closing the mold;

[0058] S52: Hold the molded material under a molding pressure of 0.3~1.0MPa for 30~120s to make the foamed blank conform to the surface of the mold cavity and form a wrapping shape that matches the motor contour;

[0059] S53: After the pressure holding is completed, release the pressure at a rate of 0.1~0.2MPa / s. After the pressure returns to zero, open the mold and take out the motor wrapping blank.

[0060] In this embodiment, the foamed preform is preheated to 80-120°C and held for 10-30 seconds. The purpose is to uniformly raise the overall temperature of the foamed preform to above the softening point of TPU but below the melting temperature. TPU is a thermoplastic elastomer whose physical cross-linked structure (hard segment micro-regions) undergoes reversible softening within the 80-120°C range. At this temperature, applying a low pressure of 0.3-1.0 MPa is sufficient to induce creep flow in the foamed preform, allowing it to conform to the mold cavity contour. The molding pressure is set to 0.3-1.0 MPa, which is much lower than the traditional injection molding or compression molding pressure (usually >10 MPa). This is because the foamed preform has a highly porous microporous structure; excessive molding pressure will crush the cell walls, leading to a decrease in closed-cell rate and deterioration of sound absorption performance. A holding time of 30-120 seconds is sufficient for the material to complete stress relaxation and shape fixation. Too short a time will result in significant springback, while too long a time will reduce production efficiency. The depressurization rate of 0.1~0.2MPa / s is to prevent the gas in the closed cells inside the foamed preform from expanding and rupturing due to excessive internal and external pressure difference during rapid depressurization, thus damaging the integrity of the cell structure.

[0061] S6: Cool the hot-pressed motor wrapping blank to room temperature to obtain the finished passenger vehicle motor wrapping.

[0062] Specifically, air cooling is used for cooling and shaping, with the cooling wind speed controlled at 2~5m / s, so that the blank of the motor package can be cooled to 20~25℃ within 10~15 minutes. During the cooling process, the blank is fixed with shaping fixtures to prevent cooling deformation.

[0063] The density of the finished passenger vehicle motor package is 25~35 kg / m³. 3 The average pore diameter is 3~15μm, and the closed-cell rate is ≥95%.

[0064] In this embodiment, air cooling is used for cooling and shaping, with a wind speed of 2-5 m / s to cool the blank to 20-25°C within 10-15 minutes. The principle for controlling the cooling rate is: excessively rapid cooling (such as direct water cooling) will cause the TPU molecular chains to not have enough time to rearrange, resulting in internal residual stress concentration and warping deformation during later storage or use; excessively slow cooling (such as natural static cooling) will result in low production efficiency. Forced air cooling at 2-5 m / s can ensure cooling efficiency while uniformly cooling the blank. A shaping fixture is used to fix the blank during the cooling process because after hot pressing at 80-120°C, the TPU is still in a highly elastic state, and the creep recovery driving force of the molecular chains has not been completely eliminated. If the constraint is removed before cooling to room temperature, the blank will partially spring back, causing dimensional deviations and preventing a tight fit with the motor housing, directly affecting the sound insulation effect. The shaping fixture keeps the blank within the shape contour given by the mold during cooling, ensuring the dimensional accuracy and shape stability of the final product.

[0065] The manufacturing process for the passenger vehicle motor enclosure of the present invention produces a finished passenger vehicle motor enclosure with a density of 25~35 kg / m³. 3 The average cell diameter is 3~15μm, and the closed-cell rate is ≥95%. Supercritical CO2 foamed TPU replaces the chemical foaming of traditional PU with physical foaming, fundamentally eliminating the adverse effects of chemical foaming agent decomposition residues on acoustic stability and environmental protection. The fine closed-cell structure of 3~15μm endows the material with excellent acoustic dissipation capabilities in the mid-to-high frequency range (800~4000Hz), which is precisely the energy concentration area of ​​electromagnetic noise and mechanical noise from electric vehicle drive motors. Compared with traditional PU foam materials (50~150μm pore size, high open-cell ratio), the present invention has thinner pore walls and significantly increased pore density. When sound waves are incident, they undergo more reflections, refractions and transmissions between a large number of fine pore walls. At the same time, the viscous friction effect and thermal conduction effect between the air in the closed pores and the pore walls are significantly enhanced, and the efficiency of sound energy conversion into heat energy is qualitatively improved. This enables the finished product to achieve a vertical incident sound absorption coefficient of over 0.6 in this frequency band, effectively solving the technical bottleneck of insufficient high-frequency sound absorption performance in existing PU foam motor wrapping parts.

[0066] Example 1:

[0067] This embodiment provides a manufacturing process for a passenger vehicle motor enclosure, including the following steps:

[0068] S1 Raw Material Drying: Polyester TPU granules (Shore hardness 85A) are fed into a hot air circulating dryer and heated to 90°C at a uniform rate of 8°C / min. The granules are then dried at a constant temperature of 90°C for 8 hours. Dry air with a dew point ≤ -40°C is introduced during the drying process. After drying, the granules are cooled to 50°C in the dry air atmosphere before being discharged. The moisture content of the granules is measured to be 0.03wt%.

[0069] S2 Extrusion Molding: The dried TPU granules are added to a single-screw extruder and melted and plasticized through multi-stage heating at 175°C in the feeding section, 190°C in the melting section, and 185°C in the homogenization section. After the molten TPU is extruded through a flat die, it is rolled and shaped by a three-roll calender to control the sheet thickness to 4mm with a thickness deviation of ≤±0.1mm, thus obtaining a continuous TPU sheet. The continuous TPU sheet is cut into rectangular sheets that match the inner cavity of the high-pressure reactor, and after standing at room temperature, the surface dust is cleaned and it is ready for use.

[0070] S3 Supercritical Saturated Impregnation: The cut TPU sheets are laid flat in layers on the material rack of the high-pressure reactor, with a 3mm gap between the layers. The reactor is sealed and the airtightness is tested to confirm that the leakage rate is ≤0.01MPa / h. Liquid CO2 is introduced into the reactor and the pressure is gradually increased to 14MPa at a rate of 0.8MPa / min, while the temperature is increased to 38℃ at a rate of 1.5℃ / min, so that the CO2 in the reactor reaches a supercritical state. The temperature and pressure are kept constant and impregnated for 24h to allow the supercritical CO2 to fully diffuse and dissolve uniformly in the TPU matrix, forming a polymer-gas homogeneous system.

[0071] S4 Pressure Reduction Foaming: After the pressure holding saturation is completed, the pressure relief valve of the reactor body is opened, and the pressure relief process is controlled by the flow regulating valve to reduce the pressure inside the reactor to normal pressure at a constant pressure reduction rate of 10MPa / s; CO2 dissolved in the TPU matrix is ​​released instantly due to the sudden drop in solubility, forming a large number of uniform bubble nuclei and growing, thus obtaining microporous foamed preform.

[0072] S5 Hot Press Molding: The foamed blank is placed flat into the molding mold cavity preheated to 100℃. After the mold is closed, it is kept at the preheated temperature for 20s. The molding pressure is maintained at 0.6MPa for 60s to make the foamed blank conform to the surface of the mold cavity and form a wrapping shape that matches the outline of the motor. After the pressure is maintained, the pressure is released at a rate of 0.15MPa / s. After the pressure is reduced to zero, the mold is opened and the motor wrapping blank is taken out.

[0073] S6 Cooling and Shaping: Air cooling is used for cooling and shaping, with the cooling wind speed controlled at 3m / s, so that the motor wrapping blank is cooled to 23℃ within 12 minutes. During the cooling process, the blank is fixed with shaping fixtures to prevent cooling deformation, and the finished product of the passenger car motor wrapping is obtained.

[0074] The finished product test results in this embodiment show a density of 30 kg / m³. 3 The average pore diameter is 8μm, the standard deviation of pore diameter distribution is ±2.5μm, the closed pore rate is 97%, and the average vertical incident sound absorption coefficient in the mid-to-high frequency band of 800~4000Hz is 0.65, of which the sound absorption coefficient at 4000Hz is 0.72.

[0075] Comparative Example 1:

[0076] The following are the specific steps for manufacturing the motor enclosure for passenger vehicles using a traditional polyurethane chemical foaming process:

[0077] The polyol component (polyether polyol, hydroxyl value 56 mg KOH / g), isocyanate component (MDI, NCO content 33.6%), chemical foaming agent (azodicarbonamide, 3 wt% of the polyol component), catalyst (triethylenediamine), and foam stabilizer (silicone oil) were mixed at a mass ratio of 100:115:3:0.6:1.2 by high-speed stirring. The mixture was then poured into a mold for motor wrapping parts preheated to 45°C and in-mold foaming and curing was carried out at 80°C for 8 hours. During this period, the chemical foaming agent decomposed and released nitrogen and carbon dioxide, which promoted the expansion and cross-linking of the polyurethane system. After curing, the mixture was demolded and allowed to cool naturally at room temperature for 24 hours until the dimensions stabilized, resulting in the finished PU foamed sound insulation pad.

[0078] Comparative Example 1: Finished product test results: density 42 kg / m³ 3 The average pore diameter is 82 μm, the standard deviation of pore diameter distribution is ±38.6 μm, the closed pore rate is 68%, and the average vertical incident sound absorption coefficient in the mid-to-high frequency band of 800~4000Hz is 0.41, of which the sound absorption coefficient at 4000Hz is 0.45.

[0079] Comparative Example 2:

[0080] PU microporous sound insulation pads were prepared using a supercritical CO2 foaming process to eliminate the interference of material system differences on performance comparison. The specific steps are as follows:

[0081] Polyether-type PU granules (Shore hardness 85A) were dried at 90℃ for 4 hours until the moisture content was ≤0.05wt%. The dried PU granules were melt-plasticized by a single-screw extruder, extruded through a flat die, and rolled and shaped by a three-roll calender to obtain PU sheets with a thickness of 4mm. The PU sheets were placed in a high-pressure reactor, CO2 was introduced and the pressure was adjusted to a supercritical state (38℃, 14MPa), and the pressure was maintained for 24 hours. The pressure was released and foamed at a depressurization rate of 10MPa / s to obtain PU microporous foamed preforms. The foamed preforms were hot-pressed at 100℃ and 0.6MPa for 60s, and after cooling, the finished PU microporous sound insulation pads were obtained.

[0082] The foaming method of this comparative example is exactly the same as that of Example 1 (supercritical CO2 foaming), except that the matrix material is different (PU replaces TPU), which is used to verify the contribution of the TPU matrix itself to the closed-cell rate and sound absorption performance.

[0083] Comparative Example 2: Finished product test results: density is 35 kg / m³ 3 The average pore diameter is 55μm, the standard deviation of pore diameter distribution is ±22.4μm, the closed pore rate is 81%, and the average vertical incident sound absorption coefficient in the mid-to-high frequency band of 800~4000Hz is 0.48, of which the sound absorption coefficient at 4000Hz is 0.52.

[0084] Comparative Example 3:

[0085] The TPU matrix was directly foamed using a chemical foaming method to eliminate the interference of differences in foaming methods on performance comparison. The specific steps are as follows:

[0086] Polyester-type TPU granules (Shore hardness 85A) were dried at 90℃ for 4 hours until the moisture content was ≤0.05wt%. The dried TPU granules were mixed at high speed with a chemical foaming agent (azodicarbonamide, 3wt%) and a nucleating agent (talc, 1wt%), and then fed into a single-screw extruder. The mixture was heated and melted in multiple stages at 175℃ (feeding section), 190℃ (melting section), and 185℃ (homogenization section) to plasticize it. The mixed melt was extruded through a flat die and then rolled and shaped by a three-roll calender. During the extrusion process, the chemical foaming agent decomposed and produced gas, causing the TPU matrix to foam and expand, resulting in a TPU chemically foamed sheet with a thickness of about 4mm. The foamed sheet was cut and then hot-pressed at 100℃ and 0.6MPa for 60s. After cooling, the finished TPU chemically foamed sound insulation pad was obtained.

[0087] The matrix material of this comparative example is exactly the same as that of Example 1 (TPU), except that the foaming method is different (chemical foaming instead of supercritical CO2 foaming), which is used to verify the contribution of the supercritical CO2 foaming method itself to the cell structure and sound absorption performance.

[0088] Comparative Example 3: Finished product test results: density is 38 kg / m³ 3 The average pore diameter is 75μm, the standard deviation of pore diameter distribution is ±30.1μm, the closed pore rate is 72%, and the average vertical incident sound absorption coefficient in the mid-to-high frequency band of 800~4000Hz is 0.44, of which the sound absorption coefficient at 4000Hz is 0.48.

[0089] Summary and comparison table of experimental data:

[0090] The test data of Example 1 were compared with those of Comparative Examples 1-3: Comparative Example 1 was a traditional PU chemical foam, with large (82 μm) and unevenly distributed pores (standard deviation ±38.6 μm), a closed-cell rate of only 68%, and a sound absorption coefficient of only 0.41. In contrast, the pore diameter of Example 1 was only 8 μm (reduced by about 90%), with a closed-cell rate of 97% and a sound absorption coefficient of 0.65 (an improvement of about 59%), verifying the overall superiority of the present invention compared with the prior art. Comparative Example 2 was foamed in the same way as Example 1 (both were supercritical CO2 foamed), only the matrix material was different (PU replaced TPU). Its closed-cell rate (81%) and sound absorption coefficient (0.48) were both lower than those of Example 1 (97%, 0.65), proving that the TPU matrix, with its higher melt strength, can more effectively maintain the integrity of the pore walls during the foaming process, and is the key material basis for obtaining a high closed-cell rate and fine microporous structure. Comparative Example 3 uses the same matrix material as Example 1 (both are TPU), differing only in the foaming method (chemical foaming instead of supercritical CO2 foaming). Comparative Example 3 has large pores (75 μm), uneven distribution (standard deviation ±30.1 μm), and a sound absorption coefficient of only 0.44. In contrast, Example 1, using supercritical CO2 foaming, achieves pore refinement down to 8 μm and a sound absorption coefficient of 0.65. This demonstrates the decisive advantage of the homogeneous nucleation mechanism of supercritical CO2 over the heterogeneous nucleation mechanism of chemical foaming in terms of pore refinement and uniformity. In summary, this invention, through the synergistic technical solution of "TPU matrix + supercritical CO2 foaming," achieves breakthroughs in pore refinement, sound absorption performance, closed-cell ratio, and environmental friendliness.

[0091] The above-disclosed embodiments are merely one or more preferred embodiments of this application and should not be construed as limiting the scope of this application. Those skilled in the art can understand that all or part of the processes for implementing the above embodiments and equivalent changes made in accordance with the claims of this application still fall within the scope of this application.

Claims

1. A manufacturing process for a passenger vehicle motor enclosure, characterized in that, Includes the following steps: The TPU granules were dried at 80~95℃, and the moisture content of the dried granules was controlled to be ≤0.05wt%. The dried TPU granules are melt-extruded and molded into TPU sheets with a thickness of 3-5mm; The TPU sheet was placed in a high-pressure reactor, CO2 was introduced and adjusted to a supercritical state, and saturated impregnation was performed at 32~45℃ and 10~18MPa for 12~36h. After saturated impregnation, the pressure inside the reactor is reduced to atmospheric pressure at a depressurization rate of 2~15MPa / s to trigger the foaming of the TPU sheet and obtain the foamed preform. The foamed blank is placed in a molding mold and heated and pressurized at 80~120℃ to form a motor wrapping blank; The hot-pressed motor wrapping blank is cooled to room temperature to obtain the finished motor wrapping for passenger vehicles.

2. The manufacturing process of the passenger vehicle motor enclosure as described in claim 1, characterized in that, The specific steps for drying the TPU granules at 80~95℃ include: The TPU granules are fed into a hot air circulating drying equipment and heated to 80-95℃ at a rate of 5-10℃ / min. Dry at a constant temperature of 80~95℃ for 6~12 hours. During the drying process, dry air is introduced to remove the moisture volatilized from the surface and inside of the granules. After drying is complete, stop heating and cool the TPU granules to 40~60℃ in a dry air atmosphere before discharging. Seal and store the material and put it into the extrusion process within 4 hours.

3. The manufacturing process of the passenger vehicle motor enclosure as described in claim 2, characterized in that, The step of melting and extruding the dried TPU granules specifically includes: The dried TPU granules are added to a single-screw extruder and melted and plasticized by multi-stage heating: feeding section 170~180℃, melting section 185~195℃, and homogenization section 180~190℃. After molten TPU is extruded through a flat die, it is rolled and shaped by a three-roll calender, and the thickness deviation of the sheet is controlled to be ≤±0.1mm to obtain a continuous TPU sheet. Cut the continuous TPU sheet into rectangular sheets that match the inner cavity of the high-pressure reactor, let it stand to room temperature, and then clean off any surface dust.

4. The manufacturing process of the passenger vehicle motor enclosure as described in claim 3, characterized in that, The method specifically includes the following steps: placing the TPU sheet in a high-pressure reactor, introducing CO2 and adjusting it to a supercritical state, and performing a saturated impregnation treatment at 32-45°C and 10-18MPa. The cut TPU sheets are laid flat in layers on the material rack of the high-pressure reactor, with a gap of 2-5mm between the layers. The reactor body is sealed and the airtightness test is completed to confirm that the leakage rate is ≤0.01MPa / h. Liquid CO2 is introduced into the reactor, and the pressure is gradually increased to 10-18 MPa at a rate of 0.5-1 MPa / min, while the temperature is increased to 32-45℃ at a rate of 1-2℃ / min, so that the CO2 in the reactor reaches a supercritical state. Maintain constant temperature and pressure, and hold the pressure for 12~36 hours to allow supercritical CO2 to fully diffuse and uniformly dissolve inside the TPU matrix, forming a polymer-gas homogeneous system.

5. The manufacturing process of the passenger vehicle motor enclosure as described in claim 4, characterized in that, The specific steps for reducing the pressure inside the vessel to atmospheric pressure at a depressurization rate of 2~15MPa / s after saturated impregnation are as follows: After saturated impregnation is completed, the pressure relief valve of the vessel is opened, and the pressure relief process is controlled by the flow regulating valve to reduce the pressure inside the vessel to atmospheric pressure at a constant pressure reduction rate of 2~15MPa / s. CO2 dissolved in the TPU matrix is ​​released instantly due to a sudden drop in solubility, forming a large number of uniform bubble nuclei and growing to obtain a microporous foamed preform.

6. The manufacturing process of the passenger vehicle motor enclosure as described in claim 5, characterized in that, The step of placing the foamed preform into a molding die and heating and pressing it specifically includes: Place the foamed preform flat into the mold cavity preheated to 80~120℃, and keep it at the preheated temperature for 10~30s after closing the mold. Hold the molded material at a molding pressure of 0.3~1.0MPa for 30~120s to make the foamed preform conform to the surface of the mold cavity and form a wrapping shape that matches the motor contour. After the pressure holding is completed, the pressure is released at a rate of 0.1~0.2MPa / s. After the pressure returns to zero, the mold is opened and the motor wrapping blank is taken out.

7. The manufacturing process of the passenger vehicle motor enclosure as described in claim 6, characterized in that, In the step of cooling the hot-pressed motor wrapping blank to room temperature, air cooling is used for cooling and shaping. The cooling wind speed is controlled at 2~5m / s, so that the motor wrapping blank is cooled to 20~25℃ within 10~15min. During the cooling process, the blank is fixed with shaping fixtures to prevent cooling deformation.

8. The manufacturing process of the passenger vehicle motor enclosure as described in claim 7, characterized in that, The density of the finished passenger vehicle motor package is 25~35 kg / m³. 3 The average pore diameter is 3~15μm, and the closed-cell rate is ≥95%.